Midwest School Psychologists’ Beliefs of Child Development Myths and Evidence-Based Statements - Hoffman, Casey B.; Latimer, Joseph; Weber, Anna M.; Axelrod, Michael I. (My University, 2018)
School psychologists are members of school teams that support students' ability to learn and teachers' ability to teach. They apply previously learned knowledge in mental health, learning, development and behavior, to help children and youth succeed in many aspects of their daily lives. With all the challenges and responsibilities school psychologists potentially have to face, they are prone to errors in thinking. School Psychologists, despite being highly intelligent and well educated are not more immune to such errors than anyone else is. The decisions that a school psychologist makes can impact students’ ability to be successful academically, behaviorally, emotionally, and socially. The adoption of pseudoscientific psychological practices in a school setting can be problematic. It is also important that all psychologists trust and embrace scientific resources in order to eliminate pseudo-scientific thinking and nonevidence based practices.
Color poster with text, charts, and graphs.
Keywords: Evidence-based research; Child development; School psychologists; Posters